Motif, dampak psikologis, dan dukungan pada korban perdagangan manusia di Nusa Tenggara Timur - Kiling, Indra Yohanes; Kiling-Bunga, Beatriks Novianti (Konsorsium Psikologi Ilmiah Nusantara, 2019)
Female adults in East Nusa Tenggara (Nusa Tenggara Timur; NTT) are at risk to be victims of national and international human trafficking. This research describes the motives, psychological impacts, and supports perceived by adult female victims from NTT. Qualitative approach was applied with thematic analysis as the analysis method. Participants were five victims of human trafficking aged between 21 – 37 years old who have returned to NTT. It was found that participants were motivated to worked outside NTT due to economical, familial, and social reasons, while some other participants also reported being forced to work abroad. The perceived psychological impacts were maladaptive behaviors, deep sadness, helplessness, and being ashamed by stigma associated with being victims. Supports that were positively meaningful were the opportunity to share with other victims and to have a counseling sessions with mental health practitioners. Initiative to improve mental health services is indispensable as a base to combat human trafficking and to support victims.